Pengaruh User Generated Content TikTok terhadap Brand Awareness Somethinc pada Generasi Z - Siregar, Anggi Khairunnisa; Diniati, Anisa (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2025)
The presence of User Generated Content (UGC) is currently a form of business communication development in the digital era. UGC is one of the communication strategies through social media, one of which is TikTok. The application of UGC has now been widely applied by companies in increasing brand awareness. This study aims to determine how much influence TikTok's social media user generated content has on Somethinc's brand awareness among Generation Z. This research tests two theories, namely user generated content, and brand awareness with eight research indicators. The method used in this research is a quantitative approach using SPSS version 25 software, with the sampling technique used is purposive sampling. The results of this study indicate that TikTok social media user generated content has a positive influence with a strong level of relationship on Somethinc brand awareness among Generation Z. User generated content contributes 48.3% to the brand awareness variable, and the remaining 51.7% is influenced by other factors not examined by the researcher.